The Right Aortic Arch with Aberrant Left Subclavian Artery as a Cause of Dysphagia Lusoria - Koc, Gonca; Doganay, Selim; Gorkem, Sureyya Burcu; Dogan, Mehmet Sait; Coskun, Abdulhakim (Journal of Nepal Paediatric Society, 2016)
The right aortic arch with aberrant left subclavian artery is a rare vascular anomaly that usually does not cause any symptoms and is encountered in the adult age group incidentally. We report a paediatric case presented with dysphagia lusoria resulted from right aortic arch with aberrant left subclavian artery with the imaging findings. J Nepal Paediatr Soc 2016;36(1):97-99.